Analysis of the characteristics of intestinal microbiota after oral tolerance in infants with food protein–induced proctocolitis - Lijing, Xiong; Mengyao, Zhou; Jing, Li; Yang, Li; Xiaoli, Xie (Frontiers in Pediatrics, 2024)
Objective: To understand the characteristics of the intestinal microbiota after oral tolerance in infants with food protein-induced proctocolitis (FPIAP) treated with amino acid formula and their differences from healthy children, aiming to provide a scientific basis for guiding the application of probiotics during treatment.Methods: FPIAP infants were prospectively enrolled, fecal specimens were obtained, and DNA was extracted for PCR amplification of the bacterial 16S rRNA gene V4 region. Library construction and sequencing were performed, and bioinformatic analysis was performed after obtaining valid data.Results: There were 36 patients in the FPIAP group: 20 males and 16 females, age 21.944±13.277 months. Diarrhea with blood in the stool were the main symptom, with an average course of 14.83±9.33 days. Thirty infants (83.33%) had mucus stool, 11.11% (4/36) of them experiencing vomiting, and 55.56% (20/36) of the infants displaying poor intake and weight gain, 28 (77.78%) patients with moderate eczema, 2 (5.6%) patients with chronic respiratory symptoms. The treatment time with amino acid formula was 5.51±2.88 months. A control group comprising of 25 healthy infants who were full-term, natural delivery, bottle fed, and matched in terms of age(24.840± 12.680 months)and gender (15 males and 10 females) was selected. Anaerobic bacteria were less abundant in FPIAP infants than healthy infants (P=4.811×10-5), but potentially pathogenic bacteria were more abundant (P=0.000). The abundance of Actinobacteria was low in FPIAP infants, the abundance of Proteobacteria was high, and the abundance of Firmicutes was reduced. Bifidobacterium could be used as a bacterial genus to differentiate healthy and FPIAP infants. Both α -and β -diversity indicators of intestinal microbiota were lower in FPIAP infants. In FPIAP infants,